2019
DOI: 10.1111/eos.12660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel prime‐and‐rinse approach on short‐ and long‐term dentin bond strength of self‐etch adhesives

Abstract: Effect of a novel prime-and-rinse approach on short-and long-term dentin bond strength of self-etch adhesives. Eur J Oral Sci 2019; 127: 547-555. © 2019 Eur J Oral SciThis study investigated the effects of the prime-and-rinse approach, using a 10methacryloyloxydecyl dihydrogen phosphate (MDP)-containing primer, on the short-and long-term dentin microtensile bond strengths (MTBSs) of mild self-etch adhesives. Half of sixty human midcoronal dentin surfaces were polished as control (self-etch approach), and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Three universal adhesives used here (TNBU, SBU, and CUBQ) contained MDP, one of the most effective functional monomers that can combine with HAp . The present NMR observations detected Ca–O–P bonds in HAp conditioned by TNBU, SBU, and CUBQ, but not in HAp conditioned by OV primer, suggesting MDP-Ca salts formed.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Three universal adhesives used here (TNBU, SBU, and CUBQ) contained MDP, one of the most effective functional monomers that can combine with HAp . The present NMR observations detected Ca–O–P bonds in HAp conditioned by TNBU, SBU, and CUBQ, but not in HAp conditioned by OV primer, suggesting MDP-Ca salts formed.…”
Section: Discussionmentioning
confidence: 55%
“…19,20 Many of today's universal adhesives incorporate the functional phosphate ester monomer 10-methacryloyloxydecyl dihydrogen phosphate (MDP), which is considered one of the most effective monomers for strong binding to HAp. 21 Another functional phosphate ester monomer that has been used in dental adhesives is glycerol phosphate dimethacrylate (GPDM), which has been utilized in E&R adhesives, SE adhesives, and self-adhesive composite cements. It is presumed that the higher etching efficacy of GPDM-based SE adhesives may result in equally effective bonding compared to phosphoric acid etching.…”
Section: Introductionmentioning
confidence: 99%
“…Some unpolymerized MDP monomer remained at the dentin surface when dentin surface was treated with MDP-containing conditioner and thoroughly water-sprayed (Li et al 2019). This mineralization induced by the MDP monomer might be limited because there was a limited amount of calcium and phosphate source at the resin–dentin interface.…”
Section: Discussionmentioning
confidence: 99%
“…This study directly demonstrated that MDP monomer with no polymeric additives could induce the biomimetic mineralization of collagen and demineralized dentin. Some unpolymerized MDP monomer remained at the dentin surface when dentin surface was treated with MDPcontaining conditioner and thoroughly water-sprayed (Li et al 2019). This mineralization induced by the MDP monomer might be limited because there was a limited amount of calcium and phosphate source at the resin-dentin interface.…”
Section: Discussionmentioning
confidence: 99%